2017
DOI: 10.1186/s12957-017-1202-8
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of tumor extent on central lymph node metastasis in solitary papillary thyroid microcarcinomas: a retrospective study of 1092 patients

Abstract: BackgroundThe morbidity of papillary thyroid microcarcinomas is increasing worldwide. Surgery is the main treatment for papillary thyroid microcarcinomas, and the choice of surgical method partly depends on the T stage of the tumor. However, according to the American Joint Commission on Cancer staging system (7th edition), the T stage of papillary thyroid microcarcinomas with different tumor extent is unclear. We aimed to study the effect of tumor extent and other factors on central lymph node metastasis to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Our results showed that there was significantly different in lymph node metastases between MTMCs group and PTMCs group. In PTMCs group, 21 (20.19%) patients had lymph node metastases, the incidence of which was similar to those in previous reports [14][15][16]. MTMCs were more likely to have lymph node metastases, which indicated the strong invasive characteristics of MTCs.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that there was significantly different in lymph node metastases between MTMCs group and PTMCs group. In PTMCs group, 21 (20.19%) patients had lymph node metastases, the incidence of which was similar to those in previous reports [14][15][16]. MTMCs were more likely to have lymph node metastases, which indicated the strong invasive characteristics of MTCs.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that there was a significant difference in lymph node metastases between the MTMC group and the PTMC group. In the PTMC group, 21 (20.19%) patients had lymph node metastases, which is similar to the incidence in previous reports [14][15][16]. MTMC patients were more likely to have lymph node metastases, which indicates the strong invasive characteristics of MTCs.…”
Section: Discussionsupporting
confidence: 87%
“…In this retrospective study, we evaluated the risk factors for CLNM and LLNM in 1,587 patients with PTMC. In previous reports, the prevalence of CLNM ranged from 24.1% to 64.1% [2][3][4][5] , and that for LLNM ranged from 3.7% to 44.5% 2 . In the present study, the prevalence of CLNM and LLNM was 30.9% (491 of 1,587) and 4.6% (73 of 1,587), respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Although PTMC has an indolent course, many cases have demonstrated highly aggressive clinical features, such as extrathyroidal extension and cervical lymph node metastasis. The incidences of central lymph node metastasis (CLNM) (24.1%-64.1%) [2][3][4][5] and lateral lymph node metastasis (LLNM) (3.7%-44.5%) 2 for PTMC are comparable with those of PTC.…”
Section: Introductionmentioning
confidence: 93%